Morphometry of the middle cerebral artery (sylvian artery) on MRI: Contribution to cerebral endovascular surgery - Racky Wade-Kane; Cheikh Seye; Magaye Gaye; Aïnina Ndiaye; Ndeye Bigué Mar; Sokhna Astou Gawane Thiam; Karim Yacouba Garba; Daouda Harouna Tireira; Isseu Dior Seck; Mamadou Ndiaye; Philippe Manyacka Manyemb; Sokhna Ba; et al. (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2022)
Introduction: The Middle Cerebral Artery (MCA), from its old nomenclature "sylvian artery", is a terminal branch of the Internal Carotid Artery (ICA) of which it constitutes the main extension. It represents a fundamental branch of the brain vasculature. The objective of this work was to provide Magnetic Resonance Imaging (MRI) morphometric data of the MCA to inform the interventions of neurovascular specialists and to contribute to the advancement of microcatheter and stent technology. Methodology: Morphometry was studied on 40 Cerebral Hemispheres (CH) of 20 right-handed subjects aged 18 to 55 years. We used a Philips MRI from the Achieva range at 1.5 Tesla with the T2-SE and TOF sequences. After identification, the MCA morphometry consisted of measuring the luminal diameter at the origins of the four segments of the MCA. These were the M1 (sphenoidal), M2 (insular or sylvian), M3 (opercular) and M4 (cortical) segments. Results: The diameter is greater at the level of the M1 segment then it decreases along the path of the MCA. Within the same HC, the average luminal diameters at the origin of segments M1, M2 and M3 decrease significantly and successively from front to back (from M1 to M3). However, there is no significant difference between the average luminal diameters of M3 and M4. The M1, M2 and M3 segments show no significant mean difference between the right cerebral hemisphere (RCH) and the Left Cerebral Hemisphere (LCH). Only the M4 segment of the MCA presents a difference in the averages of the luminal diameter between the two CHs. Also, for this same segment M4, the distribution of RCH means is significantly higher than that of LCH. Conclusion: These results can help in choosing the appropriate size (diameter) of the microcatheters. Also, they make it possible to determine new diameters of microcatheters in the neurovascular system, some distal artery segments of which have been inaccessible until now.